论台湾诗人陈肇兴的田园诗与时事诗 ：兼与陶诗的比较 = A study on Taiwanese poet Chen Chao-Hsing’s pastoral and social issues poetry : with comparison to poetry by Tao Yuanming - 雷慧媛 Loy, Hui Yuan (2014)
从1895年台湾日据时代开始，到上世纪80年代末解严，许多台湾本土文化因政治因素，遭执政者压抑。因此，很多宝贵的史料普遍不被台湾人所认知。这包括本文将谈及的台湾清领时期彰化诗人陈肇兴及其诗作。《陶村诗稿》是陈肇兴唯一留下来的作品，也是目前人们所知彰化最早的诗人别集。从其诗文中我们可了解清代中叶台湾中部的农民劳作、乡城风俗、各地景色和人民生活，最后两卷《咄咄吟》则对1862到1863年台湾三大民变之一 “戴潮春事件”有许多的记载。本篇论文探究了陈肇兴《陶村诗稿》内的作品，并将其主要分类为田园诗和时事诗，并与东晋时期陶渊明的诗作比较，找出相似之处，及陈肇兴独有的题材。陶渊明的人生过程是从入世到出世，逃离乱世之腐败，而陈肇兴则是从悠哉的田园生活转变成激进的态度。从陈肇兴前期的诗作中可看出他非常欣赏和向往陶渊明旷达的生活态度。然而，在在战火纷飞的年代挺身而出，并将时事记录于诗，是他有别于归隐的陶渊明，难能可贵的地方，值得人们研究。From 1895 when Taiwan came under the Japanese rule, till late 1980s when the imposed Martial Law was lifted, much Taiwanese local culture have been oppressed due to many political factors. This has led to many Taiwanese not knowing the island’s valuable historical data, including poems by Changhua’s Chen Chao-Hsing during the Qing Dynasty. Poetry of Tao Village is the only work collection left behind by Chen, and is the earliest known poetry collection of Changhua. His works depict farming labour, customs at the urban and rural areas, scenery, and life of the people at Central Taiwan during the mid-Qing reign. The last two volumes of the collection is named “Duoduo Yin”, which can be translated into “Tut-Tut Chants”. It mainly documents “The Case of Tai Chao-Chun”, one of the top three civil unrest in Taiwan during that period. This thesis will explore the poems in Poetry of Tao Village, and will sort them mainly into the category of pastoral poems and poems that touched upon social issues. I will also compare them to the poems by Tao Yuanming of the Eastern Jin era, finding both similarities and unique themes by Chen. Tao’s life can be summarized into two phases: from entering officialdom to exiting it, after experiencing chaos and corruption in society, whereas Chen was originally leading a carefree pastoral life, but became aggressive and radical in troubled times. From Chen’s poetry at his earlier phase of life shows that he truly admires Tao’s life attitude. However, living in a world full of distress, he did not go into seclusion like Tao, but stood up for what he believed in, also documenting the troubled situation into poems. This spirit is definitely commendable, and therefore Chen’s poetry has great research value.